Short Range Order and Static Displacements of Atoms in Polycrystalline Solid Solution of Fe-5 at. %Re - S, Enkhtur; L, Enkhtor; V.M, Silonov; Ts, Gantulga (Scientific transaction of the National University of Mongolia. Physics, 2022)
Intensity of X-ray diffuse scattering depends on scattering vector q...